Computation of electromagnetic torque in a double rotor switched reluctance motor using flux tube methods - Vaithilingam, Chockalingam Aravind; Misron, Norhisam; Zare, Mohammad Reza; Aris, Ishak; Marhaban, Mohammad Hamiruce (MDPI, 2012)
With their highly robust nature and simple design, switched reluctance machines are finding their way into numerous modern day applications. However, they produce oscillatory torque that generates torque ripple and mechanical vibrations. A double rotor structure to maximize the flux linkage and thereby increase the torque generating capability is proposed. As the machine operates close to saturation, the torque computation depends heavily on the energy conversion as the rotor rolls over the stator for a fixed pole pitch. The flux linkage characteristics are highly non-linear, hence estimation of the magnetic and mechanical parameters is extremely cumbersome. Magnetic circuit analysis by interpretation of the number of flux tubes using integration techniques at different positions of the machine to develop the flux linkage characteristics of the double rotor structure is presented. Computation of the inductances during the movement of rotor from unaligned to aligned is crucial in determining the generated torque. Relevant equations of calculations for inductance and flux linkages in the aligned, partially aligned and unaligned positions are computed. The partially aligned computation is based on the average on two intermediate positions, namely the 1/4th aligned and 3/4th aligned conditions. The static torque characteristics based on the energy conversion principles are used to compute the torque value. Results from simulation and experiments used for performance evaluation of the proposed flux tube analysis for computation of the electro-magnetic torque are presented.